Angiotensin converting enzim (ACE) gen moliforfizminin uzun mesafe koşucuları, sprinter, futbolcular ve sedenter populasyonda karşılaştırılması - Çiloğlu, Figen (My University, 2001)
Yetenek seçimi spor bilimlerinde önemli bir yer tutar. Atletizmde başarıya giden yol çok kompleks olmakla beraber, çevresel ve davranışsal faktörlerin yanı sıra genetik yatkınlıkta göz ardı edilmemesi gereken bir faktördür. Yeteneğin belirlenmesinde en erken ve objektif kriterlerin kullanılabilmesi için sportif yeteneği belirleyen gen analizleri ileriki yıllarda çok önem kazanacaktır. Atletizmde başarı için kilit faktörlerden birisi kardiovasküler performanstır. Bazı genlerin kalp ve vasküler fizyolojiyi belirledikleri düşünülmektedir. Aday genlerden biri renin-angiotensin sisteminin içindedir. Angiotensin Converting enzim (ACE) insersiyon allelinin (ACE I) dayanıklılık yeteneğini belirleyen genetik markerlerden biri olduğu düşünülmektedir. Bu çalışmada ulusal ve uluslararası düzeydeki eski ve yeni Türk erkek sporcularda Angiotensin Converting Enzim polimorfizmi belirlenmiştir. Sporcular 40 uzun mesafe koşucusu, 25 sprinter ve 30 futbolcu olarak üç gruptan oluşmuştur. Bu sonuçlar 100 sedenter, sağlıklı, Türk erkek gönüllü ile karşılaştırılmıştır. Genomik DNA deneklerin beyaz kan hücrelerinden elde edilmiş ve ACE geninin insersiyon(I) ve delesyon (D) şekilleri polimorfik bölge PCR ile çoğaltıldıktan sonra agaroz jel elektroforezi ile belirlenmiştir. Sonuçlar ki-kare ve Pearson Korelasyon testleri yapılarak karşılaştırılmıştır. Sonuçlara göre sedenter grup ile karşılaştırıldığında, uzun mesafe koşucularında ACE I alleli ve ACE I/ I genotipi fazlalıkla görülmektedir (p<0.05). Diğer yandan sprinterlerin sonuçları kontrol grubuna çok benzemektedir. Futbolcularda ise ACE I alleli ve ACE I/ I genotipi biraz daha fazlalıkla bulunsa da istatistiksel bir anlamlılık taşımamaktadır (p>0.05). Bu sonuçlara göre Türk erkek populasyonunda dayanıklılık performansı ile ACE I alleli arasında doğru orantılı bir ilişki görülmektedir ve bu testin diğer yetenek belirleme testleri ile birlikte genç sporcuyu doğru branşa yönlendirmede yararlı olacağı düşünülmektedir.

THE COMPARRISON OF ANGIOTENSIN CONVERTING ENZYME (ACE) GENETIC POLYMORPHISM AMONG LONG DISTANCE RUNNERS, SPRINTERS, FOOTBALL PLAYERS AND SEDENTARY POPULATION The ability to predict endurance performance capability plays an important role in sports science. Although making of an elite athlete is complex and includes a range of environmental and behavioral factors, genetic predisposition to athleticism might also be important. Genetic markers that contribute to the making of an elite athlete will gain even more importance in the future years. Cardiovascular performance is a key element in athletic success and certain genes are thought to be candidates for regulating cardiac and vascular physiology. One of the candidate genes is in the renin-angiotensin system. The angiotensin converting enzyme (ACE) insertion allele (ACE I) is a genetic marker that might be associated with some competitive advantage in terms of improved endurance performance. In this study ACE polymorphism was studied in past and present Turkish National male athletes who have been competing at national and international level for several years. The athletes were separated into three groups consisting of 40 long distance runners, 25 sprinters and 30 football players. The findings were compared to the results of 100 randomly selected healthy males from the sedentary Turkish population. Genomic DNA was obtained from white blood cells and the insertion (I) and deletion (D) variants of the ACE gene were identified by PCR amplification of the polymorphic region fallowed by jel electrophoresis. The results were compared using chi-square and Pearson correlation statistical analysis methods. The findings show that compared to the normal population, the long distance runners have an excess of the ACE I allele (p<0.05) and the ACE I/ I genotype (p<0.05). On the other hand, the sprinters show results very similar to the normal population. The football players show a slightly increased ACE I allele and ACE I/ I genotype but not enough to be statistically significant. These findings suggest that at least in the Turkish population, there does seem to be a positive association between endurance performance and ACE I allele and that these findings may be used along with other classical methods to steer the young athlete towards the most appropriate branch of athletics.
Keywords: SAĞLIK; SPOR-SPORCU SAĞLIĞI